The relationship between social cohession and the health status of adults in South Africa - Olamijuwon, Emmanuel Olawale (My University, 2017)
Although life expectancy has increased in South Africa (RSA), compared with other middle-income countries, health status is poor most especially among the black majority. Coupled with this are the burdens of infectious and non-communicable diseases. RSA has also shown evidence of weak social cohesion through prevalent racial and gender discrimination, income inequalities, and violence. While previous studies on the health status of adults in RSA has only examined its association with other social determinants, the relationship of adult health status and social cohesion, unlike in developed countries, remains under researched in South Africa and other African countries. Using the collective efficacy theory by Sampson and colleagues (1997), this study adds the ‘African perspective’ to the ongoing debate about the health importance of social cohesion. It examined the relationship between social cohesion and the health status of adults in South Africa. The levels and patterns of health across social cohesion and other socio-demographic characteristics were also examined. DATA AND METHODS: Data was drawn from the 2012 South African Social Attitudes Survey, a survey implemented annually by the Human Sciences Research Council. Social cohesion was assessed by drawing from the five measurable items from the work of Sampson and colleagues (1997) which encompass trust, a sense of belonging, shared values and helpless in both cash and kind. These items were subjected to principal component factor analysis with Promax rotation. Cronbach’s alpha (α) for this scale is 0.84. Scores were divided into tertiles of low, medium and high social cohesion. A cumulative stepwise logistic regression model was fitted on a weighted sample of 22,605,550 adults in South Africa aged 18 years or older to examine the nexus between social cohesion and self-rated health status. Sub-group analysis examined if the observed relationship differed by race. The data was analysed using STATA software version 14. All model diagnostics showed that the model fits reasonably for the data. The interpretation of results was made using odds ratios (ORs), and a 95% confidence was used. RESULTS: More than half of adults (54%) in South Africa reported themselves to be in good health while only about 17% reported that they were in poor health. The percentage of adults reporting good health is higher among adults in the highest tertile of social cohesion (59%), compared to 53% among those in the lowest tertile. Controlling for other characteristics, regression analysis showed that adults in lowest tertile [OR:0.70, CI:0.516 - 0.965] and moderate tertile [OR:0.79, CI:0.589 - 1.055] of social cohesion were less likely to report moderate or good health compared to adults in the highest tertile of social cohesion, but the relationship was only statistically significant among adults in the lowest tertile of social cohesion. Sub-group analysis by race showed that among all the racial groups (excluding Indian or Asian adults), black African [OR:0.68, CI:0.472-0.989], coloured [OR:0.63, CI:0.305-1.309], and white [OR:0.67, CI:0.293 1.545] adults residing in the lowest tertile of social cohesion were less likely to be in moderate or good health compared to those in the highest tertile of social cohesion, but the relationship was only statistically significant among black Africans. CONCLUSION AND RECOMMENDATION: The findings from this study demonstrate that social cohesion among adults in South Africa, particularly among black Africans, is important for improvement in health. It is therefore important that the government of South Africa intensifies efforts aimed at increasing social cohesion among adults, particularly among black Africans. This could be achieved through public awareness on the health importance of social cohesion and the need for neighbours to share similar values, trust one another and be willing to help. This is especially important if significant progress is to be made in achieving the sustainable development goals to improve the health of adults in the country by 2030.
A research report submitted to the Schools of Public Health and Social Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the award of the Degree of Masters of Arts in the Demography and Population Studies
Keywords: Social groups--Health aspects--South Africa; Health--Social aspects--South Africa; Socialization--South Africa